Effects of Y - Course Mobile Application on Knowledge, and Perceived Efficacy for Following Up, and Rehabilitation Among Patients with Schizophrenia of Village Health Volunteers in Yingo District, Narathiwas Province - Akaji ์Nirusnee; Islamthamthada, Mariam; Benno, Salahuddin (Princess of Naradhiwas University Journal, 2024)
One group pre - posttest quasi experimental study examined the effects of Y -course mobile application on knowledge, perceived efficacy for follow up, and rehabilitation among patients with schizophrenia in six skills. It also assessed satisfaction level of village health volunteers in district with the use of the Y-course mobile application. 45 village health volunteers were selected as samples to serve as subdistrict representatives by using multistage random selection. Instruments utilized as follows: 1) The Y-course mobile application; 2) instruments for data collection comprised the following four components: 1) A general personal questionnaire; 2) a questionnaire concerning assessment, care, and rehabilitation skills; 3) an evaluation of the perceived efficacy using a symptom monitoring questionnaire; and 4) a satisfaction questionnaire was surveyed regarding the Y-course mobile application. The contents of these instruments were validated by five experts. These instruments had a CVI index of 0.95. The knowledge measurement test’s reliability of KR-20 equaled 0.92. Alpha Cronbach’s coefficient of perceived efficacy assessment reliability was 0.84. Data analysis was conducted by using descriptive statistics and Pair t-test. Findings revealed that knowledge and perceived efficacy for following up and rehabilitation among patients with schizophrenia of village health volunteers in Yingo district, Narathiwas province, were statistically significantly higher after using the Y-course mobile application than before using the program. The perceived efficacy for following up, and rehabilitation among patients with schizophrenia was in the moderate level prior to using the Y-course mobile application. Following use of the application, the score level was in a good level. The Y-course mobile application yielded a good overall satisfaction score.